Dampak Dinamika Penduduk Terhadap Pola Ruang Kecamatan Sukarame Tahun 2014-2022 - Azzam, Muhammad Fachir; Rahman, Yudha (Jurnal Perencanaan dan Pengembangan Kebijakan, 2024)
The development of a city occurs along with the development and changes in land that are triggered by the dynamics of the population. Population dynamics can occur as a result of births, deaths and population movements that affect changes in the number, composition and growth of the population. This study aims to identify the impact of population dynamics on spatial patterns. To achieve these objectives, this research uses mixed methods, namely quantitative methods combined with qualitative methods. To determine the impact of population dynamics on spatial patterns, this study uses simple linear regression analysis. Research on this analysis uses the variable Population Dynamics as an independent variable that gives effect. Also using the variables of changes in spatial patterns, that receive the impact of influential variables. The results of the regression analysis of the impact of population dynamics on spatial patterns show that population dynamics only have an effect of 26.7% on spatial pattern changes. This analysis proves that population dynamics do not have a significant impact on spatial patterns. The initial hypothesis of this study, namely population dynamics has an impact on spatial patterns and spatial structure, has been proven through regression analysis that this hypothesis can be accepted because population dynamics has an impact on spatial pattern, although it is not significant.